Pengaruh Penggunaan Media Audio Visual Terhadap Kemampuan Menulis Cerita Pendek Tema Pesantren Kelas Xi Smk Nurul Huda Buay Madang - Anam, Syaiful; Rifa’i , Muhamad Nanang; Adella Novita (Gayaku Publisher, 2024)
This study aims to determine the improvement of short story writing ability of grade XI students of SMK Nurulhuda Buaymaadang Sukaraja. The purpose to be achieved in this study is to describe the effect of using Aidio Visual media on the ability to write short stories on the theme of Islamic boarding school students in class XI of SMK Nurul Huda BuayMadang. This research was conducted in August 2024 at SMK Nurul huda Buay madang Sukaraja. In this study, the research objectives were the XI grade students of SMK Nurulhuda Buaymaadang Sukaraja. Data collection in this study was observation, tests and documentation. The research method used is pre experimental design. A one group before-after plan (one group pretest-postest design) data analysis technique that uses validity test, reliability test, normality test and hypothesis test (t test). in this study using one class, namely class XI Accounting with a sample of 22 students. From the research results obtained data on the experimental class pretest average value of 75.5 and the posttest average value of 80.2. The paired sample t-test results obtained a significance value of 0.081 <0.05 which means Ho is rejected and Ha is accepted. Based on the results of the data analysis obtained, it is concluded that learning by using Audio Visual media can have an influence on the ability to write short stories of class XI students of SMK Nurulhuda Buay madang Sukaraja.